Greater (V)over dotO(2peak) is correlated with greater skeletal muscle deoxygenation amplitude and hemoglobin concentration within individual muscles during ramp-incremental cycle exercise - Okushima, D.; Poole, David C.; Barstow, Thomas J.; Rossiter, H. B.; Kondo, N.; Bowen, T. S.; Amano, T.; Koga, S. (My University, 2017)
It is axiomatic that greater aerobic fitness ((V)over dotO(2peak)) derives from enhanced perfusive and diffusive O-2 conductances across active muscles. However, it remains unknown how these conductances might be reflected by regional differences in fractional O-2 extraction (i.e., deoxy [Hb+Mb] and tissue O-2 saturation [StO2]) and diffusive O-2 potential (i.e., total[Hb+Mb]) among muscles spatially heterogeneous in blood flow, fiber type, and recruitment (vastus lateralis, VL; rectus femoris, RF). Using quantitative time-resolved near-infrared spectroscopy during ramp cycling in 24 young participants ((V)over dotO(2peak) range: similar to 37.4-66.4 mL kg(-1) min(-1)), we tested the hypotheses that (1) deoxy [Hb+Mb] and total[Hb+Mb] at (V)over dotO(2peak) would be positively correlated with (V)over dotO(2peak) in both VL and RF muscles; (2) the pattern of deoxygenation (the deoxy[Hb+Mb] slopes) during submaximal exercise would not differ among subjects differing in (V)over dotO(2peak). Peak deoxy [Hb+Mb] and StO2 correlated with (V)over dotO(2peak) for both VL (r = 0.44 and -0.51) and RF (r = 0.49 and -0.49), whereas for total[Hb+Mb] this was true only for RF (r = 0.45). Baseline deoxy[Hb+Mb] and StO2 correlated with (V)over dotO(2peak) only for RF (r = -0.50 and 0.54). In addition, the deoxy[Hb+Mb] slopes were not affected by aerobic fitness. In conclusion, while the pattern of deoxygenation (the deoxy[Hb+Mb] slopes) did not differ between fitness groups the capacity to deoxygenate [Hb+Mb] (index of maximal fractional O-2 extraction) correlated significantly with (V)over dotO(2peak) in both RF and VL muscles. However, only in the RF did total [Hb+Mb] (index of diffusive O-2 potential) relate to fitness.
Citation: Okushima, D., Poole, D. C., Barstow, T. J., Rossiter, H. B., Kondo, N., Bowen, T. S., . . . Koga, S. (2016). Greater (V)over dotO(2peak) is correlated with greater skeletal muscle deoxygenation amplitude and hemoglobin concentration within individual muscles during ramp-incremental cycle exercise. Physiological Reports, 4(23), 12. doi:10.14814/phy2.13065
Keywords: Diffusive Oxygen Potential; Fractional Oxygen Extraction; Peak Oxygen; Uptake; Time-Resolved Nirs; Near-Infrared Spectroscopy